New double‐layer design for 1‐stage repair of orocutaneous and pharyngocutaneous fistulae in patients with postoperative irradiated head and neck cancer. (24th June 2015) - Sadigh, Parviz L.; Wu, Cheng‐Jung; Feng, Wen‐Jui; Hsieh, Ching‐Hua; Jeng, Seng‐Feng
Abstract: Background: The development of a postoperative orocutaneous fistula (OCF) or pharyngocutaneous fistula (PCF) in the irradiated tissues of patients with head and neck cancer represents a high burden of morbidity for the patient. With high postoperative recurrence rates, these fistulae result in a reconstructive challenge for the plastic surgeon. In this study, we propose a new double‐layer design to successfully repair these fistulae in a 1‐stage reconstruction. Methods: Twelve patients with an average age of 56 years (range, 45–67 years) were operated on between January 2006 and December 2012 using this double‐layer single‐stage technique. All patients had received postoperative radiotherapy after their initial reconstruction. A circumferential turnover flap was designed and raised from the skin surrounding the fistula to recreate inner lining using a tension‐free, water‐tight repair. No debridement of the fistula itself was performed. The second‐layer of the reconstruction, which represents the outer lining, was achieved with either a local or a free flap. Results: Fistula size ranged from 0.8 × 0.5 cm to 3 × 3.2 cm with a mean size of 2 cm 2 . The outer lining was achieved using a free flap in 5 cases and a local flap in 7 cases. All the flaps survived completely with no cases of postoperative infection, however, 1 case was complicated by mandibular plate exposure necessitating its removal. No major complication or recurrence has yet been encountered in any of our patients with a mean follow‐up of 28 months (range, 12–78 months). Conclusion: This 1‐stage double‐layer design can provide a reliable and relatively straightforward means of repairing OCF and PCF in the irradiated tissues of patients with head and neck cancer. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E353–E359, 2016